1987
DOI: 10.1177/000456328702400204
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Horseradish Peroxidase and Alkaline Phosphatase-Labelled Antibodies in Enzyme Immunoassays

Abstract: The periodate method was found to be most effective for preparing horseradish peroxidase-sheep anti-human and horseradish peroxidase-donkey anti-mouse immunoglobulin (IgG) conjugates. The conjugates were improved by carrying out the oxidation of the enzyme at low pH. Anti-human and anti-mouse IgG-peroxidase conjugates (0·5 mg/mL IgG and 0.7 mg/mL 19G, respectively) were used at 1:15 000 and 1:8000 dilutions, respectively, in a sandwich ELISA to detect human and mouse IgG in buffer or in a growth medium contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…A benefit of using a red chromogen is the ability to readily distinguish the cytoplasmic staining of melanocytes from pigmented keratinocytes and melanophages. However, enzyme‐linked immunosorbent assay studies have shown a decreased ability to detect low abundance antigen using alkaline phosphatase enzymatic assay (red), as compared to a horseradish peroxidase assay (brown); 21 therefore, we used a brown chromogen in our studies.…”
Section: Discussionmentioning
confidence: 99%
“…A benefit of using a red chromogen is the ability to readily distinguish the cytoplasmic staining of melanocytes from pigmented keratinocytes and melanophages. However, enzyme‐linked immunosorbent assay studies have shown a decreased ability to detect low abundance antigen using alkaline phosphatase enzymatic assay (red), as compared to a horseradish peroxidase assay (brown); 21 therefore, we used a brown chromogen in our studies.…”
Section: Discussionmentioning
confidence: 99%
“…Standard scrum with a known amount of specific anti body and the test scrum samples were added to wells and incubated overnight at 4°C. After washing the plates 3 times with PBS-Twcen, affinity-purified rab bit anti-p-lactoglobulin IgG, previously conjugated with biotin [21], was added. The development of color was performed with streptavidin-biotinylated horse radish peroxidase complex, using tetramethylenebenzidine as substrate.…”
Section: Methodsmentioning
confidence: 99%
“…1 University of California. lecular and intermolecular cross-links, both to couple already associated species (36,37); and to join various proteins, which might or might not otherwise associate, in order to combine the properties of both into a single molecule, e.g., to make protein-protein conjugates (38,39), enzyme-linked antibodies (40,41), immunotoxins (42,43), and drug-protein conjugates (44). A large number of reagents that have been developed to serve these and a variety of other purposes are commercially available.…”
mentioning
confidence: 99%